Case Report: Hemophagocytic Lymphohistiocytosis Prior to the Onset of Leukemia in a Boy With CDK13-Related Disorder - Cui, Dongyan; Wang, Songmi; Zhang, Ai; Liu, Aiguo; Hu, Qun (Frontiers in Genetics, 2022)
Cardinal features of CDK13-related disorders are characterized by intellectual disability, developmental delay, dysmorphic facial features, structural heart defect and structural brain abnormality. A 9-year-old boy presented with intellectual disability, development delay, characteristic craniofacial features, brain malformation, cryptorchidism, autism spectrum disorder, and recently, recurrent hemophagocytic lymphohistiocytosis (HLH) in a half year period. Further investigation revealed the diagnosis of CDK13-related disorder. Finally, we found the underlying cause of HLH is acute lymphoblastic leukemia. Probably leukemia was a coincidental finding in this boy with CDK13-related disorder, but the case herein suggests that individuals with CDK13-related disorder also face risk of developing cancers. Further detailed information could enable us to clarify this presentation because of only limited investigation in affected cases.